2023
DOI: 10.3233/jad-220765
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Kidney Function with Plasma Amyloid-β Levels and Brain Amyloid Deposition

Abstract: Background: Reduced kidney function is related to brain atrophy and higher risk of dementia. It is not known whether kidney impairment is associated with higher levels of circulating amyloid-β and brain amyloid-β deposition, which could contribute to elevated risk of dementia. Objective: To investigate whether kidney impairment is associated with higher levels of circulating amyloid-β and brain amyloid-β deposition. Methods: This cross-sectional study was performed within the community–based Atherosclerosis Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Furthermore, it is important to evaluate the effects of clinical confounders and biological factors on the clinical diagnostic and prognostic performance of GFAP for AD (Hansson et al, 2022). Previous studies preliminarily found that impaired kidney function could affect the concentration of amyloid 1-42, p-tau181, and NfL but not plasma GFAP (Sedaghat et al, 2023;Zhang et al, 2023); however, more comprehensive studies with larger cohorts are still needed to explore the effect of more factors, such as peripheral neuropathies and body mass index, on blood GFAP for more accurate laboratory measurements and clinical interpretation (Hansson et al, 2022). By this bibliometric analysis, it was also found that the USA, China, England, Japan, Spain, Germany, and Sweden contributed the most research on GFAP within the area of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is important to evaluate the effects of clinical confounders and biological factors on the clinical diagnostic and prognostic performance of GFAP for AD (Hansson et al, 2022). Previous studies preliminarily found that impaired kidney function could affect the concentration of amyloid 1-42, p-tau181, and NfL but not plasma GFAP (Sedaghat et al, 2023;Zhang et al, 2023); however, more comprehensive studies with larger cohorts are still needed to explore the effect of more factors, such as peripheral neuropathies and body mass index, on blood GFAP for more accurate laboratory measurements and clinical interpretation (Hansson et al, 2022). By this bibliometric analysis, it was also found that the USA, China, England, Japan, Spain, Germany, and Sweden contributed the most research on GFAP within the area of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated higher AD biomarker levels in CKD without clear association with cerebral amyloid deposition. 30 , 32 Thus, elevated AD biomarker levels in CKD may be due to lower elimination of these biomarkers by the kidneys rather than improvement in cerebral amyloid pathology. Although we did not evaluate cerebral amyloid in this study, it is hard to imagine a near complete resolution of amyloid deposits in a 12‐week period.…”
Section: Discussionmentioning
confidence: 99%
“…ICU patients frequently develop post-ICU syndrome with a spectrum of chronic cognitive impairments reminiscent of AD; the persistent elevations of Aβx-40 plasma level in both ICU cohorts observed at time of admission to 7 days later may be a contributing factor. Considering that Aβx-40 has been shown to be the primary form of soluble Aβ excreted in urine [ 52 ], it will be important for future studies to determine whether increasing Aβx-40 plasma levels are due to a shift in excretion caused by kidney dysfunction. Of additional interest, sepsis causes long-lasting, trained innate immunity that increases Aβ-induced cognitive impairments in mice [ 53 ].…”
Section: Discussionmentioning
confidence: 99%